Renewable resources-based approach to biantennary glycolipids - Tabandeh, Mojtaba; Salman, Abbas Abdulameer; Goh, Ean Wai; Heidelberg, Thorsten; Hussen, Rusnah Syahila Duali (Elsevier, 2018)
A new synthesis approach towards biantennary lipids of Guerbet glycoside type was developed based on oleic acid as sustainable resource. Functionalization of the double bond provided access to primary alcohols with α-branched C19-skeleton. Formulation studies with corresponding lactosides indicated formation of vesicles with high assembly stability. A relatively narrow bimodal size distribution of the latter, which turns into a narrow unimodal distribution of small vesicles upon addition of an ionic cosurfactant, suggests potential for a vesicular drug delivery system.